Evaluation of univariate integrals via fluctuationlessness theorem - (:unkn) unknown (My University, 2008)
A recently developed Fluctuation Method is used in approximating the remainder term of the integral of the Taylor expansion. This provides us with a new numerical integration method. © 2008 American Institute of Physics.
Keywords: Fluctuation expansion; Numerical integration; Taylor polynomials